2012
DOI: 10.1093/eurheartj/ehs426
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and risk of death from vascular and non-vascular causes in the Whitehall study and meta-analyses of 12 000 deaths

Abstract: Despite strong inverse and apparently independent associations of 25(OH)D with vascular and non-vascular mortality, causality remains uncertain. Large-scale randomized trials, using high doses of vitamin D, are required to assess the clinical relevance of these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 32 publications
1
69
0
5
Order By: Relevance
“…A partir de esa fecha, un número grande de estudios han informado que las concentraciones adecuadas de 25(OH)D se asocian con menor prevalencia de diabetes, hipertensión, dislipidemia y síndrome metabólico [6][7][8][9] . Por otra parte, se ha reportado asociación de la deficiencia de 25(OH)D con mayor prevalencia de EAC asintomática 10 y con eventos cardiovasculares como infarto del miocardio 11 y mortalidad de causa cardiovascular y no vascular 12 . Sin embargo, existen varios estudios que no han encontrado asociación entre la deficiencia de esta vitamina y la enfermedad cardiovascular 13,14 .…”
Section: Introductionunclassified
“…A partir de esa fecha, un número grande de estudios han informado que las concentraciones adecuadas de 25(OH)D se asocian con menor prevalencia de diabetes, hipertensión, dislipidemia y síndrome metabólico [6][7][8][9] . Por otra parte, se ha reportado asociación de la deficiencia de 25(OH)D con mayor prevalencia de EAC asintomática 10 y con eventos cardiovasculares como infarto del miocardio 11 y mortalidad de causa cardiovascular y no vascular 12 . Sin embargo, existen varios estudios que no han encontrado asociación entre la deficiencia de esta vitamina y la enfermedad cardiovascular 13,14 .…”
Section: Introductionunclassified
“…A growing literature (1)(2)(3) suggests that vitamin D may be associated with reduced mortality (overall (4) and hospital-associated (5) ), incidence of cancer (6)(7)(8)(9)(10)(11)(12)(13) , CVD (14,15) , diabetes (16) , fractures (17,18) and ageing-related functional limitations (19) , although some studies find an unclear relationship (20,21) or a harmful association with disease (22) . Randomized controlled trials are underway to examine the potential role of vitamin D in the prevention of multiple diseases, including cancer, CVD and diabetes (20,23) .…”
Section: Introductionmentioning
confidence: 99%
“…The Whitehall study conducted a 13-year follow up of approximately 5409 older adults and reported that higher concentration of vitamin D was inversely and linearly correlated with both vascular and nonvascular disease mortality and that doubling of serum vitamin D concentration was associated with significant reduction in the mortality rates. 82 Similarly, the Copenhagen city heart study examined approximately 10,170 Danish adults in 1981-1983 for baseline cardiovascular risk factors and diseases and during a 29 year longitudinal follow up indicated that lower vitamin D level was associated with a 64% higher risk of myocardial infarction, 57% higher risk of premature mortality and 81% higher risk of fatal ischemic heart disease. 83 Thus vitamin D deficiency is associated with significant mortality and morbidity from chronic diseases.…”
Section: Neuropsychiatric Conditionmentioning
confidence: 99%